Parameters of low back pain chronicity among athletes: Associations with physical and mental stress. (September 2016) - Heidari, Jahan; Mierswa, Tobias; Kleinert, Jens; Ott, Ida; Levenig, Claudia; Hasenbring, Monika; Kellmann, Michael
Abstract: Objective: In the general population, physical and mental stress factors are linked to chronic low back pain (LBP). The aim of the present study was to examine this association among athletes. Design: Longitudinal study with a six-month interval between measurements. Setting: Questionnaires were filled out at home, either in paper–pencil version or online. Participants: Eighty-two male and 57 female athletes ( N = 139, M Age = 32.24) who exercise on a competitive ( n = 102) or recreational level ( n = 37), with a weekly training volume of at least 3 h. Main outcome measures: At T0, stress parameters were assessed via the Recovery-Stress Questionnaire (RESTQ-Basic-48) and the Screening Scale of the Trier Inventory for the Assessment of Chronic Stress (TICS-SSCS). At T0 and T1, different chronification indicators were measured. Based on these assessments, the sample was split into a chronification and no-chronification group. Results: ANCOVAs were used to conduct group comparisons with regard to stress levels. The chronification groups showed higher stress values for all chronification indicators. For the variables Physical Complaints and Overall Stress-TICS, the group differences became significant ( p < .05). Conclusion: A relationship between stress parameters and LBP chronification was demonstrated among athletes for the first time. Highlights: Low back pain (LBP) chronification is associated with stress in athletes. Physical stress plays a predominant role for athletes' perceived pain. The findings pronounce the value of biopsychosocial approaches for LBP in athletes. Monitoring of athletes' stress seems to be important to prevent chronic LBP.